Book Review of Dead Poets Society Written by N.H. Kleinbaum - Ariyani, Linda Dwi (LANTERN (Journal on English Language, Culture and Literature), 2015)
This review analyzes the strengths and weaknesses of N.H. Kleinbaum’s Dead Poets Society. Dead Poets Society is a novel that tells a story about a journey of an English literature teacher who provides non-conventional teaching methods in literature. This review explores the strengths and the weaknesses of N.H. Kleinbaum’s Dead Poets Society by reviewing its elements. They are theme, plot, and characters. This novel has strengths that make it as a good reading. The strengths of the novel are theme and plot. The weakness of the novel is the character aspect. The author tells too much about the additional figures. The goal of this study is to understand the novel clearly. Therefore, the reader can know the opinion of the author about the content of the novel.